Speech therapy practice to patients in palliative care: an integrative review (Research, Society and Development, 2020)
The speech therapist can actively contribute within the multidisciplinary team of Palliative Care through assessment, prevention and rehabilitation, thus favoring the safety and efficiency of swallowing, communication, minimizing aspects that interfere in the quality of life of the subject under palliation. The objective of this study was to analyze the scientific production on speech therapy activities to patients in palliative care and discuss the strategies of speech therapy activities to patients in palliative care. This is an exploratory and descriptive research, consolidated an integrative literature review that aimed to analyze the scientific production on speech therapy to patients in palliative care. Once the descriptor associations were made in the databases, 25 articles were found and selected 06. After analyzing these articles, two categories were created: speech-language disorders in patients in Palliative Care; Speech therapy intervention strategies for patients in Palliative Care. Speech therapy can intervene, seeking the comfort and quality of the patient's pathway in palliative care and, also, providing a greater possibility of interaction between the patient, family, caregivers, information and health professionals through communication. As strategies that facilitate communication, the speech therapist can focus on direct therapy with the patient, the training of communication facilitators with the family and caregivers and the use of alternative means as a form of communication, such as: gestures and non-verbal communication, communication boards, computer systems and prostheses. In conclusion, speech therapy is important as a member of the multidisciplinary team in the care of patients in palliative care, since they can identify disorders that these patients may develop during treatment and which may lead to the insertion of this individual in a critical situation of terminality.